Digital Novels: A Recycled Advertisement about the Old Social Construction of Women’s Identity - Magdalena Baga (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
21st-century digital novels, accessible through mobile apps like Webnovel, Dreame, and Play Books, commonly depict women characters as powerless, impoverished stepdaughters or illegitimate children. These prevalent themes in digital novels often reinforce patriarchal norms and present themes of fathers' financial struggles and indebtedness to wealthy families resulted to contract marriage or planned marriage. Employing the approach of feminist literary criticism, this study aims to examine how these novels uphold antiquated perceptions of women's identity. Through the reading strategy of feminist literary criticism is revealed that these digital novels represented the old construction about women identity, perpetuating the idea that women are powerless and financially dependent on men. From the setting of the novel, we know that the offered themes were not only occurred in eastern culture but also in western culture. They depict women as inanimate objects, lacking agency and voice. The narratives promote patriarchy by portraying male power and oppression as protection, often emphasizing material wealth. This notion is strategically disseminated through digital novels, targeting the millennial generation who have easy access to digital media. Consequently, younger women may internalize these ideas and accept their subjugated role. Instead, digital novels should empower women to navigate patriarchal constraints and depict men who respect and support women's autonomy, challenging traditional gender norms. While the study employs feminist literary criticism as the reading strategy, it's important to acknowledge that different theoretical frameworks or approaches may provide alternative interpretations of the novels. Recognizing the limitations and potential biases of the chosen methodology could lead to a more balanced analysis.